Long-Term Mortality among Hospitalized Adults with Sepsis in Uganda: A Prospective Cohort Study - Abdullah Wailagala; Stephen Okello; Willy Kayondo; Rodgers R. Ayebare; David F. Olebo; Mubaraka Kayiira; Melissa Gregory; Stacy M. Kemigisha; Jeff W. Koehler; Randal J. Schoepp; Helen Badu; Nehkonti Adams; et al. (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Twelve-month mortality in sepsis survivors has not been previously characterized in sub-Saharan Africa. Hospitalized adults with ≥2 modified systemic inflammatory response syndrome criteria (temperature 38°C, heart rate ≥90 beats per minute, or respiratory rate ≥20 breaths per minute) were enrolled at a tertiary care center from October 2017 to August 2022. Multiple clinical blood and respiratory molecular and antigen assays were used to identify infectious etiologies. Baseline demographics were evaluated for risk of death by 1 month and 12 months using Cox proportional hazards regression. Among 435 participants, the median age was 42.0 years (interquartile range: 28.0–57.0 years), 59.1% were female, and 31.7% were living with HIV. Malaria (17.2%), followed by tuberculosis (4.6%) and bacteremia (4.6%), were the most common detected causes of illness. Overall, 49 (11.3%) participants died, and 24 participants died within 1 month to 1 year (49.0% of deaths). Female participants had a decreased risk of death by 12 months (unadjusted hazard ratio: 0.38; 95% CI: 0.21–0.68). The mortality of sepsis may be underestimated in sub-Saharan Africa because nearly half of deaths occurred after the first month, underscoring the need for long-term follow-up.